Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Loyalitas Pelanggan Ms Glow Palembang - Rizkiana, Rina; P, Charisma Ayu (Universitas Multi Data Palembang, 2024)
This research was conducted to see the effect of service quality and product quality on customer loyalty at Ms. Glow Palembang. The sample size taken was 267 respondents with purposive sampling method. The data analysis technique used in this study was multiple linear regression analysis method with SPSS Statistics 21 software carried out to analyze the research data. The partial test results (t test) show the results of Service Quality has a significant value of 0.000 <0.05. and product quality variables have a significant value of 0.000 <0.05. Service Quality and Product Quality in the simultaneous test (f test) simultaneously have a significant effect on customer loyalty with a sig number of 0.000 <0.05.